Mr Topaze - Sellers, Peter 1925-1980; De Grunwald, Dimitri; Lom, Herbert 1917-2012; Gray, Nadja 1923-1994; MacKern, Leo 1920-2002; Whitelaw, Billie 1932-2014; Le Mesurier, John 1912-1983 (British Film Institute, 2018)
"Peter Sellers directs and stars in this bittersweet character comedy, based on a Marcel Pagnol play and chosen by the British public in 2016 to be digitised by the BFI. Described by Sellers' biographer Roger Lewis as a 'lost classic', Mr Topaze marked the actor's directorial feature debut and teamed him with his The Ladykillers cohort and future Pink Panther comic foil Herbert Lom, in a stellar cast that also features Nadia Gray, Leo McKern, Billie Whitelaw and John Le Mesurier. Playing the eponymous Mr Topaze, a poor, provincial French schoolteacher slowly corrupted by big business, Sellers is at the peak of his powers. This melancholy character comedy, rarely seen since its release and available here for the first time on Blu-ray and DVD, is essential viewing for fans of Sellers' unique genius."
Dual format edition
Original: UK, 1961
Bildformat 2.35:1
Special features: Let’s go crazy (1951, 33 mins): a nightclub-set madcap variety show featuring Peter Sellers and Spike Milligan ; The running jumping & standing still film (1960, 11 mins): Richard Lester and Peter Sellers’ Goonish comic short, featuring Sellers, Spike Milligan and Leo McKern ; Film star: Peter Sellers (1967, 37 mins): a profile of the actor and comedian ; Maurice Woodruff interview (1967, 19 mins): Peter Sellers’ favourite clairvoyant interviewed by Bernard Braden for a TV series, Now and then, that was never made ; John Boulting interview (1967, 21 mins): the director discusses his relationship with Sellers in an unbroadcast Now and Then interview with Bernard Braden ; Peter Sellers at the NFT (1960, 97 mins, audio only): the actor addresses an enthusiastic throng of fans ; Abigail McKern interview (2019, 20 mins): the daughter of Leo McKern discusses the great actor’s life and career ; The poetry of realism (2019, 13 mins): journalist Kat Ellinger’s video essay on Marcel Pagnol, the writer of the film’s theatrical source, Topaze
Verlagsnummer BFIB1328
Keywords: Film; Blu-Ray-Disc; DVD-Video